A Study of a Microstrip Patch Antenna With a Drilled Through-Holes Array Structure Based on the Line Source Analysis Method - Ding, Zhendong; Zhang, Dan; Ma, Chunyu (Frontiers in Physics, 2020)
A novel periodic photonic crystal structure with through-holes drilled by a 4 × 7 array based on the line source analysis method was proposed in this paper to improve the gain and radiation of the microstrip antenna. The analysis results showed that, with the help of the line source analysis method, this through-hole structure could improve the gain and radiation of the antenna. The proposed through-hole structure was superior to other periodic structures. The sizes of the antenna and the patch used were 46.86 × 60.86 × 1.6 mm and 20.43 × 30.43 mm, respectively. Through-holes were made on three distinct layers: the patch, dielectric, and ground layers. The resulting operating frequency was 2.95 GHz, the bandwidth ranged from 84.7 MHz to 2.9085–2.9932 GHz, the return loss was 40.9455 dB, the voltage standing wave ratio (VSWR) was 1.011, and the maximum gain was 4.88 dBi. The return loss of the through-hole design was 69.1% higher than that of the structure without holes and 18.3% higher than that of the simulated structure. The gain increase of 58.4% was relatively non-porous. Good agreement between simulation and measurement could be observed, indicating that the proposed structure was effective. Its operating band can be used in radio navigation systems and positioning systems (2.9–3 GHz).